Drivers of the level of market participation among smallholder urban vegetable farmers in KwaZulu-Natal, South Africa - P. N. Ndlovu; J. M. Thamaga-Chitja; Temitope Oluwaseun Ojo (Cogent Food & Agriculture, 2024)
Urban farming has gained significant recognition and interest in less developed countries as it has the potential to address challenges linked to rapid urbanization, unemployment, and food insecurity. This study aimed to determine the drivers of market participation and the level of market participation among smallholder urban vegetable farmers in the Sobantu and Mphophomeni township areas. Primary data were collected using a structured questionnaire. A multi-stage sampling technique was used to sample 156 smallholder urban vegetable farmers. The data were analyzed using descriptive statistics, and a double-hurdle model. The results 18 indicated that out of a total of 156 smallholder farmers, 127 farmers were market participants and 29 were non-participants. The logistic model result indicated that market participation decision among smallholder urban farmers was significantly influenced by credit use (p = 0.004), free inputs (p = 0.096), access to market information (p = 0.001), access to labour (p = 0.014), and owning a smartphone (p = 0.083). Fractional response model results indicated that the level of market participation among smallholder urban vegetable farmers were significantly influenced by age (p = 0.093), cooperative membership (0.002), road condition (p = 0.001), storage (p = 0.016), and distance to input markets (0.069). The study concludes that market participation can be enhanced by increasing the market. information sources through market-empowered extension services and improved access to market information including through targeted radio, television, and the Facebook application. The study recommends urban agriculture policies and programs by various stakeholders that Strengthen market training activities and form farmer co-operatives to meet market requirements and improve market participation among smallholder urban farmers.